Importance of Safety in a Workshop at Schools for a Safe and Effective Teaching and Learning Sessions - Vengidason, Sethuprakash; Mat Nashir, Irdayanti; Jing , Rui Tang; Ismail, Mohammed Amiruddin; Nallaluthan, Kesavan; Subramaniam, Tamil Selvan (Journal of Technical Education and Training, 2021)
Dangerous situations can develop at any time in a workshop if the people who use the workshop are not alert. It can be very dangerous even though a simple mistake occurs when the safety procedures are compromised. This research aims to obtain the perception and comments from students regarding their knowledge about workshop safety in schools. The objective of this research is to acquire the perception and comments from Faculty of Technical and Vocational, Sultan Idris Education University students. There are 5 different questions distributed among the students for them to give their judgements. This study is an interview based approach. The data was collected by distributing the questions to 148 students and 35 student’s answers were randomly picked to be analysed. The students are expected to give their perception and comments based on their knowledge and observation about workshop safety and its practises in secondary schools. Results show that, around 40% of the students feel that all the teachers know about safety in workshop to avoid an accident from occurring. Some students commented that teachers need to enlighten the students about safety because many of them are not practising it at the fullest. Many students feels that first aid kit is the main instrument which must be kept in a workshop in the event of accident occurs. The conclusion is, knowledge about workshop safety is good but it must be practised by students and teachers in all schools to minimize injuries and damages.